2021
DOI: 10.3390/cancers13215268
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Glioblastoma Cells’ Sensitivity to Oncolytic Viruses

Abstract: Oncolytic viruses have gained momentum in the last decades as a promising tool for cancer treatment. Despite the progress, only a fraction of patients show a positive response to viral therapy. One of the key variable factors contributing to therapy outcomes is interferon-dependent antiviral mechanisms in tumor cells. Here, we evaluated this factor using patient-derived glioblastoma multiforme (GBM) cultures. Cell response to the type I interferons’ (IFNs) stimulation was characterized at mRNA and protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 58 publications
(71 reference statements)
0
32
0
Order By: Relevance
“…To explore the DirectMS1Quant sensitivity for quantitative description of cellular response to stimuli, two glioblastoma, GBM3821 and GBM4114, and the astrocyte (AN) cells treated with interferon alpha (IFN α ) were used. Earlier it has been demonstrated that AN and GBM3821 cells respond to IFN α by upregulation of dozens of IFN-induced proteins, while GBM4114 has impaired interferon-dependent antiviral mechanisms and does not respond to IFN stimulation 23 . In this work, IFN response of these cellular models was quantified using different workflows shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To explore the DirectMS1Quant sensitivity for quantitative description of cellular response to stimuli, two glioblastoma, GBM3821 and GBM4114, and the astrocyte (AN) cells treated with interferon alpha (IFN α ) were used. Earlier it has been demonstrated that AN and GBM3821 cells respond to IFN α by upregulation of dozens of IFN-induced proteins, while GBM4114 has impaired interferon-dependent antiviral mechanisms and does not respond to IFN stimulation 23 . In this work, IFN response of these cellular models was quantified using different workflows shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…MS/MS-based analysis of glioblastoma samples was performed using Q-Exactive HF mass spectrometer (Thermo Fisher Scientific, San Jose, CA, USA). Experimental label-free data for DDA mode were published elsewhere 23 . Experimental data for TMT were acquired in two ways: single-shot LC-MS/MS runs and deep proteome analysis with sample pre-fractionation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations